EFEKTIVITAS PELAKSANAAN PERATURAN DAERAH KOTA MAKASSAR NOMOR 3 TAHUN 2016 TENTANG PEMBERIAN AIR SUSU IBU (ASI) EKSKLUSIF - Hanan Khasyrawi Abrar; Musakkir Musakkir; Hamzah Halim (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2020)
This study aims to determine and understand the implementation of Makassar City Government Regulation Number 3 of 2016 concerning Exclusive Breastfeeding; and the factors that influence the effectiveness of implementing exclusive breastfeeding to newborn babies in Makassar. this research is empirical research or socio-legal research. The results of this study indicate that: The effectiveness of Makassar City Regulation Number 3 Year 2016 Regarding Exclusive Breastfeeding is still very low due to the fundamental problem that most new mothers have a lack of understanding related to Exclusive Breastfeeding and the influence of traditions that are not appropriate or culture of the community. In addition, exclusive breastfeeding is only compliance that is compliance or identification, in other words, even though most new mothers give birth directly, exclusive breastfeeding seems to obey the law or local regulations, but the size or quality of the effectiveness of those regional regulations can still be questioned because mothers who give birth only give exclusive breastfeeding because of medical indications or early in the birth. The factors that influence the implementation of Bylaw No. 3 of 2016 concerning Exclusive Breastfeeding are legal factors, namely, it is not yet clear the comprehensive rules in the Perda regarding the substance of the rules such as sanctions against counselors who do not carry out their duties. Furthermore, law enforcement factors namely, the lack of oversight functions carried out by related parties, especially the Makassar City Health Office. Facilities and infrastructure factors, namely, lack of availability of adequate and non-standard lactation rooms. Then, the community factor which has been ignoring regulations and tends to be passive in supporting the government's efforts in disseminating information on exclusive breastfeeding.